Evolution of DNAase I Hypersensitive Sites in MHC Regulatory Regions of Primates. Issue 2 (18th April 2018) - Jin, Yabin; Gittelman, Rachel M; Lu, Yueer; Liu, Xiaohui; Li, Ming D; Ling, Fei; Akey, Joshua M
Abstract: Jin et al. report thousands of DNAseI hypersensitive sites in the MHC region that have been gained or lost in primate genomes since their evolutionary divergence, identifying 24 that evolved rapidly in the human lineage... It has been challenging to determine the disease-causing variant(s) for most major histocompatibility complex (MHC)-associated diseases. However, it is becoming increasingly clear that regulatory variation is pervasive and a fundamentally important mechanism governing phenotypic diversity and disease susceptibility. We gathered DNase I data from 136 human cells to characterize the regulatory landscape of the MHC region, including 4867 DNase I hypersensitive sites (DHSs). We identified thousands of regulatory elements that have been gained or lost in the human or chimpanzee genomes since their evolutionary divergence. We compared alignments of the DHS across six primates and found 149 DHSs with convincing evidence of positive and/or purifying selection. Of these DHSs, compared to neutral sequences, 24 evolved rapidly in the human lineage. We identified 15 instances of transcription-factor-binding motif gains, such as USF, MYC, MAX, MAFK, STAT1, PBX3, etc ., and observed 16 GWAS (genome-wide association study) SNPs associated with diseases within these 24 DHSs using FIMO (Find Individual Motif Occurrences) and UCSC (University of California, Santa Cruz) ChIP-seq data. Combining eQTL and Hi-C data, our results indicated that there were five SNPs located in human gains motifs affecting the corresponding gene's expression, two of which closely matched DHS target genes. In addition, a significant SNP, rs7756521, at genome-wide significant level likely affects DDR expression and represents a causal genetic variant for HIV-1 control. These results indicated that species-specific motif gains or losses of rapidly evolving DHSs in the primate genomes might play a role during adaptation evolution and provided some new evidence for a potentially causal role for these GWAS SNPs.